2013
DOI: 10.5194/bgd-10-17859-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Picoplankton community structure before, during and after convection event in the offshore waters of the southern Adriatic Sea

Abstract: Abstract. This paper documents the picoplankton community's response to changes in oceanographic conditions in the period between October 2011 and September 2012 at two stations belonging to South Adriatic Pit (SAP). The recorded data include the community's abundance, composition, prokaryotic production rates and bacterial metabolic capacity. The aforementioned interval included an intense sea cooling with formation of exceptionally, record-breaking dense water. We documented an especially intense winter conv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…As expected, these were associated with the typical seasonal maximum of primary production. Winter in the Adriatic usually has been described as a time of weak stratification and low plankton production (Kršinić, 1998;Benović et al, 2005;Cerino et al, 2012;Najdek et al, 2014). Surprisingly, this was not the case in the winter of 2015, when zooplankton abundance was higher than previously observed (Table 2).…”
Section: Unusual Zooplankton Bloomcontrasting
confidence: 52%
See 1 more Smart Citation
“…As expected, these were associated with the typical seasonal maximum of primary production. Winter in the Adriatic usually has been described as a time of weak stratification and low plankton production (Kršinić, 1998;Benović et al, 2005;Cerino et al, 2012;Najdek et al, 2014). Surprisingly, this was not the case in the winter of 2015, when zooplankton abundance was higher than previously observed (Table 2).…”
Section: Unusual Zooplankton Bloomcontrasting
confidence: 52%
“…Picophytoplankton dominates the phytoplankton community in the southern Adriatic and appears to be its main primary producer (Najdek et al, 2014;Babić et al, 2017), while microphytoplankton production is restricted to coastal waters, the deep chlorophyll maximum, and periods during or following winter convection (Gačić et al, 2002;Batistić et al, 2012;Cerino et al, 2012;Ljubimir et al, 2017). Winters in the southern Adriatic are characterized by convection events and vertical mixing that recur regularly, supporting the nutrient enrichment of the surface waters that enhances phytoplankton development (Batistić et al, 2012, Ljubimir et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that in the Mediterranean Sea satellite-based Chla estimates could not be accurate in several instances, such as during the stratification period when sub-surface Chla accumulations are very common 59 , during the specific moments when DC happens as large Chla values could be spread down to several hundred meter depth 75 or into some coastal areas 76 . However, for the spring time and for the analysed area, previous modelling works have shown that surface Chla concentration is quite homogeneous in the first 100 m 59 so, for the purposes of the comparisons shown in here, satellite data could be considered accurate enough.…”
Section: Discussionmentioning
confidence: 99%
“…Although the massive presence of autotrophs in deep layers have been previously documented, and linked to the passive downslope-transport of surface cells facilitated by NAdDW 35 , in our study such characteristics was not exclusive of DWs but was general even for resident deep water masses. In February 2012 an intense winter convective episode, influencing the whole water column through vertical mixing processes, was registered in the South Adriatic Pit and in its surroundings 10 . Such hydrographic process, known to be responsible for the transport of nutrients from deep-sea reservoirs to the surface and of organic matter from the surface to deep waters, could explain the occurrence of high biomass of autotrophic organisms even in the aphotic layers, up to 400–600 m depth 7 .…”
Section: Discussionmentioning
confidence: 99%
“…DSWC off the shelf break has been recognized as having a major role in bringing oxygen to deep water masses 3 and, by providing cross-shelf transport of organic matter, nutrients, oxygen and organisms, it has the potential to change the biodiversity of deep-sea communities, affecting biogeochemical cycles, and influencing the overall deep-sea functioning 3 5 . Although some studies have documented episodic changes of abundance, biomass and composition of plankton along water column as result of winter convective events 6 10 , studies on the effects of shelf DW advection on the plankton communities are still insufficient. Yoder and Ishimaru 11 reported unusual high concentrations of phytoplankton (especially of two diatoms, Skeletonema costatum and Asterionella japonica ) in DW cascaded off the southeastern United States continental shelf, at depths higher than 100 meters.…”
Section: Introductionmentioning
confidence: 99%